2012
DOI: 10.1123/ijspp.7.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Even Between-Lap Pacing Despite High Within-Lap Variation During Mountain Biking

Abstract: Purpose:Given the paucity of research on pacing strategies during competitive events, this study examined changes in dynamic high-resolution performance parameters to analyze pacing profiles during a multiple-lap mountain-bike race over variable terrain.Methods:A global-positioning-system (GPS) unit (Garmin, Edge 305, USA) recorded velocity (m/s), distance (m), elevation (m), and heart rate at 1 Hz from 6 mountain-bike riders (mean ± SD age = 27.2 ± 5.0 y, stature = 176.8 ± 8.1 cm, mass = 76.3 ± 11.7 kg, VO2ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Theoretically, an even pacing pattern is regarded as optimal for performance in endurance sports events with durations > 2 min, where athletes race against the clock over a known distance ( Abbiss and Laursen, 2008 ). In contrast, studies of running ( Tucker et al, 2006 ; Hanley, 2015 ), cycling ( Thomas et al, 2012 ), mountain bike ( Martin et al, 2012 ), and rowing ( Garland, 2005 ) have shown that athletes, in fact, apply positive, J-shaped or variable pacing patterns. Furthermore, studies on pacing patterns in XC ski racing have consistently shown that, on a lap-by-lap basis, XC skiers apply a positive pacing pattern independent of both race distance and level of the skiers ( Larsson and Henriksson-Larsen, 2005 ; Bolger et al, 2015 ; Formenti et al, 2015 ; Andersson et al, 2016 ; Losnegard et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%
“…Theoretically, an even pacing pattern is regarded as optimal for performance in endurance sports events with durations > 2 min, where athletes race against the clock over a known distance ( Abbiss and Laursen, 2008 ). In contrast, studies of running ( Tucker et al, 2006 ; Hanley, 2015 ), cycling ( Thomas et al, 2012 ), mountain bike ( Martin et al, 2012 ), and rowing ( Garland, 2005 ) have shown that athletes, in fact, apply positive, J-shaped or variable pacing patterns. Furthermore, studies on pacing patterns in XC ski racing have consistently shown that, on a lap-by-lap basis, XC skiers apply a positive pacing pattern independent of both race distance and level of the skiers ( Larsson and Henriksson-Larsen, 2005 ; Bolger et al, 2015 ; Formenti et al, 2015 ; Andersson et al, 2016 ; Losnegard et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, any notable changes in number of bouts and the mean duration of bouts did not follow the decrease in accumulated W' per lap and mean bout magnitude (Table 2). The lack of a meaningful change in bout duration and number suggests high PO actions are a result of challenges imposed by the track, in support of Martin et al (2012) conclusions about a spontaneous relationship between pacing and terrain, with even lap-to-lap pacing despite high intralap variability. Another aspect could be that the decrease in mean bout magnitude is simply a response to the reduced density of riders after the mass-start (Granier et al, 2018).…”
Section: Measurementioning
confidence: 76%
“…CP is considered to be the highest sustainable rate of oxidative metabolism without a continuous loss of homeostasis, defined as the boundary between steady state and non-steady state exercise ( Poole et al, 1988 ; Jones et al, 2008 ). Applying the CP concept to XCO could thus delineate work attributable to aerobic and anaerobic energy sources during a race ( Chidnok et al, 2012 ; Martin et al, 2012 ; Hays et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed during cycling (Faria et al, 2005;Davies et al, 2016). To date, no data exists for fixed-gear bike events and very few studies have explored similar cycling events in short closed circuits such as cyclo-cross (Bossi et al, 2018) or mountain bike (Martin et al, 2012;Granier et al, 2018;Moss et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In mountain bike cycling, pacing has been shown to be related to performance, age, sex, and race experience (Moss et al, 2019). Even or positive pacing strategies are generally observed in official races or laboratory simulated events (Martin et al, 2012;Bossi et al, 2018;Moss et al, 2019). In addition, fast starts are often observed (Bossi et al, 2018;Granier et al, 2018;Viana et al, 2018) and large within-laps variability has been observed partly as a result of topography (Martin et al, 2012;Moss et al, 2019).…”
Section: Introductionmentioning
confidence: 99%